Polyphenolic QTOF-ESI MS Characterization and the Antioxidant and Cytotoxic Activities of Prunus domestica Commercial Cultivars from Costa Rica - Navarro Hoyos, Mirtha (2021)
There is an increased interest in plum research because of their metabolites’ potential bioactivities. In this study, the phenolic profiles of Prunus domestica commercial cultivars (Methley, Pisardii and Satsuma) in Costa Rica were determined by Ultra Performance Liquid Chromatogra phy coupled with High Resolution Mass Spectrometry using a quadrupole-time-of-flight analyzer (UPLC-ESI-QTOF MS) on enriched phenolic extracts obtained through Pressurized Liquid Extraction (PLE) under acidic and neutral extraction conditions. In total, 41 different phenolic compounds were identified in the skin and flesh extracts, comprising 11 flavan-3-ols, 14 flavonoids and 16 hydrox ycinnamic acids and derivatives. Neutral extractions for the skins and flesh from all of the cultivars yielded a larger number of compounds, and were particularly rich in the number of procyanidin trimers and tetramers when compared to the acid extractions. The total phenolic content (TPC) and antioxidant potential using the DPPH and ORAC methods exhibited better results for neutral extracts with Satsuma skins and Methley flesh, which showed the best values (685.0 and 801.6 mg GAE/g extract; IC50 = 4.85 and 4.39 µg/mL; and 12.55 and 12.22 mmol TE/g extract, respectively). A Two-Way ANOVA for cytotoxicity towards AGS gastric adenocarcinoma and SW620 colon adenocar cinoma indicated a significant difference (p < 0.05) for PLE conditions, with better results for neutral extractions, with Satsuma skin delivering the best results (IC50 = 60.7 and 46.7 µg/mL respectively) along with Methley flesh (IC50 = 76.3 and 60.9 µg/mL, respectively). In addition, a significant positive correlation was found between TPC and ORAC (r = 0.929, p < 0.05), as well as a significant negative correlation (p < 0.05) between TPC and cytotoxicity towards AGS and SW620 cell lines (r = −0.776, and −0.751, respectively). A particularly high, significant, negative correlation (p < 0.05) was found between the number of procyanidins and cytotoxicity against the AGS (r = −0.868) and SW620 (r = −0.855) cell lines. Finally, the PCA clearly corroborated that neutral extracts are a more homogenous group exhibiting higher antioxidant and cytotoxic results regardless of the part or cultivar; therefore, our findings suggest that PLE extracts under neutral conditions would be of interest for further studies on their potential health benefits.